Akulturasi Budaya Jawa dan Islam dalam Tradisi Dugderan di Masjid Agung Kauman Semarang: Bentuk, Makna dan Proses Historis - amalia, Finta; Muh Maula Ulil Absor; Muhammad Azizi Muslih; Fajar Adhim Nugraha; Lutfi Adil Fatih; Olivia Sofvi; M Rikza Chamami (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2025)
Abstract: The Dugderan tradition in Semarang City is a cultural phenomenon rich in acculturation values between Javanese and Islamic culture. This study aims to describe its forms, analyze its meanings and values, and identify the historical process of acculturation within the Dugderan tradition centered at the Kauman Great Mosque of Semarang. Using a qualitative-historical approach, this study finds that Dugderan functions not only as an official marker for the beginning of the Ramadan fasting period, but also as a contextual medium of da'wah and a unifying force for a multicultural society. The most prominent expressions of acculturation appear in the symbols of Warak Ngendog and the ritual processions of “dug” (drum beating of the bedug) and “der” (cannon). The values contained include tolerance, self-purification (wara') before Ramadan, and joy. Historically, this tradition originated in 1881 AD during the reign of the Regent of Semarang, Raden Mas Tumenggung Aryo Purbaningrat, as an effort to unite differences in determining the beginning of the fast among Muslims in Semarang. This research contributes to the literature on Nusantara Islamic studies and the preservation of local cultural heritage. Abstrak: Tradisi Dugderan di Kota Semarang merupakan fenomena budaya yang kaya akan nilai akulturasi antara Budaya Jawa dan Islam. Penelitian ini bertujuan mendeskripsikan bentuk-bentuk, menganalisis makna dan nilai, serta mengidentifikasi proses historis akulturasi dalam tradisi Dugderan yang berpusat di Masjid Agung Kauman Semarang. Menggunakan pendekatan kualitatif- historis , studi ini menemukan bahwa Dugderan berfungsi tidak hanya sebagai penanda resmi dimulainya ibadah puasa Ramadan, tetapi juga sebagai media dakwah yang kontekstual dan pemersatu masyarakat multikultural. Wujud akulturasi yang paling menonjol tampak pada simbol Warak Ngendog dan prosesi ritual 'dug' (bedug) dan 'der' (meriam). Nilai-nilai yang terkandung mencakup toleransi, kesucian diri (wara') menjelang Ramadan, dan kegembiraan (sukacita). Secara historis, tradisi ini berawal sejak tahun 1881 Masehi pada masa pemerintahan Bupati Semarang Raden Mas Tumenggung Aryo Purbaningrat , sebagai upaya menyatukan perbedaan penentuan awal puasa di kalangan umat Islam Semarang. Penelitian ini memberikan kontribusi pada literatur studi Islam Nusantara dan pelestarian warisan budaya lokal.